2007
DOI: 10.1051/0004-6361:20077505
|View full text |Cite
|
Sign up to set email alerts
|

Low-lying magnetic loops in the solar internetwork

Abstract: Aims. We study the structure of the magnetic field vector in the internetwork and search for the presence of small-scale loops. Methods. We invert 1.56 µm spectropolarimetric observations of internetwork regions at disc centre by applying the SIR code. This allows us to recover the atmospheric parameters that play a role in the formation of these spectral lines. We are mainly interested in the structure of the magnetic field vector. Results. We find that many opposite polarity elements of the internetwork are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 16 publications
7
67
0
Order By: Relevance
“…Such fields, partly seen in the internetwork regions by Hinode (e.g. Lites et al 2007), are very likely small loops (Centeno et al 2007;Martínez González et al 2007) and may be due to a local dynamo (Vögler & Schüssler 2007;Schüssler & Vögler 2008). It is unclear if such low-lying loops really influence the structure of the higher-lying chromosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Such fields, partly seen in the internetwork regions by Hinode (e.g. Lites et al 2007), are very likely small loops (Centeno et al 2007;Martínez González et al 2007) and may be due to a local dynamo (Vögler & Schüssler 2007;Schüssler & Vögler 2008). It is unclear if such low-lying loops really influence the structure of the higher-lying chromosphere.…”
Section: Discussionmentioning
confidence: 99%
“…presented in Martínez González et al 2007). The present emergence rate is almost seven times higher than the rate inferred from IMaX data using the Fe i visible line at 525 nm at ∼0.15…”
Section: Observationsmentioning
confidence: 99%
“…Below that we generally speak of "ephemeral regions" (10 18 to 10 20 Mx). Even smaller are the smallest so far resolved bipolar features, the internetwork magnetic loops (Martínez González et al 2007;Centeno et al 2007;Martínez González and Bellot Rubio 2009;Danilovic et al 2010a) which emerge throughout the QS (although preferring a meso-scale pattern). They have fluxes of roughly 10 16 to 10 17 Mx (Lin and Rimmele 1999) and display in general weak equipartition (that is, the magnetic energy density is similar to the kinetic energy density of the convective flows) intrinsic fields.…”
Section: Magnetic Flux Emergencementioning
confidence: 99%
“…Martínez González et al (2007), using data from VTT, found low-lying photospheric magnetic loops connecting about 10 to 20 % of the visible magnetic flux of opposite polarity. Note that emerging small-scale loops are observed in the form of newly detected horizontal fields well before vertical flux is detected (see Centeno et al 2007, for a corresponding study based on Hinode/SOT-SP data).…”
Section: Photospheric Quiet-sun Loopsmentioning
confidence: 99%
See 1 more Smart Citation